Grieves and struggles of family caregivers providing care for bedridden elderly patients affected by chronic degenerative diseases - Campos , Joice Soares; dos Anjos , Anna Cláudia Yokoyama; Neto , Sebastião Benício da Costa; Peres , Rodrigo Sanches (Investigación y Educación en Enfermería, 2021)
Objective. To understand grieves and struggles of family caregivers providing care for bedridden elderly patients affected by chronic degenerative diseases. Methods. This cross-sectional study was developed following the guidelines of the clinical-qualitative method. The sample was composed of 10 female family caregivers of bedridden elderly patients affected by chronic degenerative diseases in a city in the interior of Minas Gerais, Brazil. The sample size was determined by data saturation. The instruments used included semi-structured interviews and a field diary. The audio-recorded interviews were transcribed verbatim and submitted to content analysis. The field diary provided contributions to the organization of categories, conferring a more accurate context. Results. The participants experienced two types of grief, one for the loss of a “healthy family member” and the other for the “announced death” of this person. Additionally, the participants faced two main struggles: overcoming (objective and subjective) fatigue and becoming fully capable of performing their roles. Conclusion. The family caregivers of bedridden elderly patients affected by chronic degenerative diseases experience grieves and struggles that should be taken into account from the beginning of the care process through mental health actions intended to meet their needs.